Handbuch der deutsch-jüdischen Literatur - Horch, Hans Otto (De Gruyter, 2016)
Research activity on German-language literature by Jewish authors has intensified, especially since the 1970s. However, until now there has been no single work to compile and evaluate this body of literary work. This Handbook successfully fulfills this need. A historical section addresses the course of German-Jewish literature since the beginning of the Enlightenment, and a systematic section is devoted to the presentation of specific genres.